BS EN 60512-99-002 Ed.2.0. Connectors for electrical and electronic equipment. Tests and measurements. Part 99-002. Endurance test schedules. Test 99b: Test schedule for unmating under electrical load (22nd December 2020) - British Standards Institution,
No abstract available